INFLUENCE OF COGNITIVE BIASES ON CONSUMER BUYING BEHAVIOUR (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
All human beings without exception, are in  some way or the other, consumers of goods  & services. Thus, a day in the life of a person  is full of consumer decisions. Cognitive bias  can have a significant impact on the decisions  and judgments people make, often resulting in  deviations from rational thinking and decision  making. This applies to consumer decisions as  well. Marketing literature mentions cognitive  biases that influence consumer decision making.  The present paper focuses on six cognitive biases  that affect decision making of consumers & tries  to study their influence on a consumersacross  demographic factors. It also investigates which  bias / biases exert the major influence on the  buying process, how consumers view their own  buying behaviour & how marketers use the  cognitive biases for their advantage. The paper  is based on empirical research.
Keywords: Cognitive bias; consumer buying behaviour; confirmation bias; anchoring effect; loss aversion